Critical Analysis of the New Horizons of 21st Century Urdu Novels - Dr. Tahir Nawaz; Dr. Ghulam Farida; Dr. Aqlima Naz (Al-Qanṭara, 2025)
In the 21st century, the changing global scenario, the provision of the internet, and the common man’s access to Western literature have ushered in a new era in Urdu novel writing, which includes modern themes, diverse narratives, and aesthetic experiences. In this century, Urdu novels are more prominent than other genres, as they not only reflect contemporary regional issues but also try to adapt to global influences while staying connected to their rich cultural heritage. The digital era has also played a key role in the new horizon of Urdu novels. The advent of e-books and online publishing platforms has made Urdu literature more accessible to a global audience. Writers can now break down geographical barriers and reach readers worldwide. Social media platforms have further facilitated this exchange, allowing writers to engage directly with their readers and get instant feedback. This interaction has not only helped writers improve their art but has also encouraged a more vibrant and interactive literary culture. Urdu novelists have given new dimensions to novel writing by combining traditional storytelling with modern literary techniques and the reach provided through digital platforms. This research article will critically examine the "New Horizons of Urdu Novels in the 21st Century".